Pijat Punggung dan Akupresur untuk Produksi ASI pada Ibu Postpartum Multipara: Quasi Eksperimen - Triwidayanti Triwidayanti; Mardiana Ahmad; Andi Wardihan Sinrang; Andi Nilawati Usman; Saidah Syamsuddin; Muh Aryadi Arsyad; Nur Aliya Arsyad (Faletehan Health Journal, 2023)
Exclusive breastfeeding is essential for developing physical, psychological, and intellectual development. However, coverage of exclusive breastfeeding from 0-6 months is still low locally, nationally, and globally. The problem which mothers frequently complained, namely less or unsmooth breastmilk production, can be solved by a back massage and acupressure. This research aimed to analyze the influence of back massage and acupressure on breastmilk production in multiparous postpartum mothers. This study used quasi-experimental method with posttest only design. The samples of this study were 30 multiparous postpartum mothers who were distributed evenly into back massage group and acupressure group. All interventions were done once a day for 30 minutes in seven days. The samples were selected by using purposive sampling technique. The instruments used were observation form, SOP sheet of back massage and acupressure, and Postpartum Depression Screening Scale (PDSS) questionnaire. The data analysis used independent t-test. The research results showed the average of breastmilk production after intervention in the group of back massage back (597.67 nm/dl) was lower than acupressure group (687.33 nm/dl), which means there was a difference between back massage and acupressure to enhancement of breastmilk production with p value 0.007. Back massage and acupressure could help multiparous postpartum mothers who experience a lack of breastmilk and were helpful for mothers who experience breastfeeding problems at the previous childbirth.